Empowerment of Bricklayers through Lightweight Brick Production Training in Makassar City - Nurlita Pertiwi; Nur Anny Suryaningsih Taufieq; Irma Aswani Ahmad; Dyah Darma Andayani (ABDIMAS: Jurnal Pengabdian Masyarakat, 2024)
The urgency of this Community Service activity is to overcome the limitations of the economic capacity of bricklayers due to productivity challenges. The main problem in the initial survey results illustrates the high risk of job loss for bricklayers as seasonal workers. Most bricklayers are unemployed for three to four months a year. This activity aims to improve the knowledge and skills of bricklayers in making lightweight bricks. These skills will be useful in economic opportunities for bricklayers when they are unemployed. The implementation of the training, which is divided into two parts, namely education about lightweight bricks and training in making lightweight bricks, took place effectively with the involvement of 25 bricklayers. The activity evaluation results showed that most participants were skilled in preparing materials and tools, mixing mortar, and molding lightweight bricks.